GW24-e1857 Nucleosome Assembly Protein 1-like 1 Knockdown Promotes Cardiomyocytes Differentiation by Mesoderm Induction through Notch Signalling in Mouse Induced Pluripotent Stem Cells. (1st October 2013) - Hui, Gong; Yan, Yuan; Xue, Yuanyuan; Yin, Peipei; Ding, Zhiwen; Zhang, Guoping; Yang, Chunjie; Ge, Junbo; Zou, Yunzeng
Abstract : Objectives: Although induced pluripotent stem cells (iPSCs)-derived cardiomyocytes are expected as the potential source of cell-based therapy for heart diseases, the rate of derivation is too low for clinical application. Recently, we used a functional proteome analysis to screen out nucleosome assembly protein 1-like 1 (Nap1l1) which was downregulated during the differentiation of P19CL6 cells into cardiomyocytes. We here attempted to study the role of Nap1l1 in the cardiogenesis of iPSCs. Methods: The role of Nap1l1 in iPSCs was examined by RNA interference via lentiviral vectors encoding a short hairpin RNA (shRNA). Furthermore, we established overexpression iPSCs by transfecting lentiviral vetcors integrated Nap1l1 cDNA sequence and the empty lentiviral vectors were transfected to iPSCs as control. Results: We observed Nap1l1 was downregulated during the differentiation of iPSCs. Knockdown of Nap1l1 dramatically enhanced the differentiation of iPSCs into cardiomyocytes characterised by the increased number of beating embryonic bodies (EBs), the larger alpha-myosin heavy chain (α-MHC)-stained area and the upregulation of cardiac transcription factors (Nkx2.5, GATA4, Mef2c, Tbx5). The effects were sharply inhibited by Nap1l1 overexpression in iPSCs. Cardiomyocytes derived from Nap1l1-knockdown-iPSCs exhibited proper cell biological characteristics judged from subcellular structure and their response to neurohormonal triggers. Further study revealed that Nap1l1 negatively induced mesoderm (Flk-1, Brachyury and Mesp1) development. However, the same number of mesoderm stem cells (Flk-1positive cells) from Nap1l1-knockdown-, Nap1l1-overexpressed or their control-iPSCs didn't show obvious difference in cardiomyocyte differentiation. Next study indicated that Nap1l1 positively regulated Notch intracellular domain (NICD) and downstream genes during differentiation of iPSCs. Notch signalling inhibitor greatly rescued the inhibitory effects of Nap1l1 on mesoderm induction and cardiogenesis. Conclusions: These findings demonstrate that downregulation of Nap1l1 significantly enhances mesodermal induction and subsequently promotes cardiogenesis from mouse iPSCs via regulating Notch signaling, which will facilitate application of iPSCs to heart diseases.